A Case of Ascending Aorta and Arch Replacement for Impending Ruptured Atherosclerotic Arch Aneurysm Combined with Chronic Dissecting Ascending Aortic Aneurysm - Taniguchi, Iwao; Yamaga, Takeshi; Suzuki, Yoshimasa; Kamihira, Satoshi; Nakamura, Yoshinobu (Japanese Journal of Cardiovascular Surgery, 2000)
We report a 78-year-old man who had an impending ruptured atherosclerotic arch aneurysm combined with chronic dissecting ascending aortic aneurysm. The patient underwent a graft replacement of the ascending aorta and aortic arch using the elephant trunk method with the aid of profound hypothermia and continuous retrograde cerebral perfusion. Cerebral blood velocity was measured with transcranial Doppler (TCD) during operation. The TCD flow pattern after weaning of cardiopulmonary bypass indicated a state of brain edema. Therefore it is important in extensive retrograde cerebral perfusion to control the perfusion pressure and prevent destruction of the blood brain barrier aggressively. Pharmacological intervention could improve the safety of retrograde cerebral perfusion. Postoperative diagnostic images showed that the part of the distal anastomosis around the elephant trunk was not surrounded with thrombus. At this stage, it is not necessary to perform next extensive aortic replacement. It is important to consider the occurrence of complication, who using elephant trunk method, including paraplegia, thromboembolism, kinking of prothesis.